Adaptation responses of different ecotypes of Leymus chinensis to saline–alkaline stress - Li, Ya-Xiao; Ma, Hong-Yuan; Ni, Hong-Wei; Li, Shao-Yang; Xu, Lu; Sun, Meng-Dan; Qi, Wen-Wen; Zhao, Dan-Dan (Frontiers in Ecology and Evolution, 2024)
Soil salinity-alkalinity has emerged as a global problem affecting many ecosystems, including grassland. Plants evolve into different ecotypes to adapt to various environments. Leymus chinensis widely distributed in the eastern Eurasian steppe, has evolved into two main ecotypes: yellowgreen(YG) and gray-green(GG). Studies on the adaption mechanisms of both ecotypes in response to saline-alkaline stress are limited. In this study, the growth and physiological traits of ecotypes YG and GG in soils with different salinity-alkalinity levels-severe saline-alkaline soil (SS), moderate saline-alkaline soil (MS), and light saline-alkaline soil (LS)-were studied. After exposure to saline-alkaline stress for 15 months, the L. chinensis ecotypes exhibited significant differences in the growth characteristics. The specific leaf area, individual tiller biomass, net photosynthetic rate, and potassium content of the two ecotypes under MS conditions were significantly higher than or similar to those under LS conditions. This indicates that L. chinensis showed a certain degree of tolerance to saline-alkaline environments under MS conditions. Salinealkaline stress increased the tillers by 56% in GG and reduced them by 26% in YG, and did not alter the SLA and the number of individual tiller leaves of GG but reduced that of YG. Moreover, with increasing levels of saline-alkaline stress, ecotype GG exhibited an increase in net photosynthetic rate (Pn), while ecotype YG showed insignificant changes. Under SS, GG exhibited higher Pn and chlorophyll content than YG.Additionally, with the increase in the saline-alkaline stress level, the Na + content increased, but GG exhibited a significantly lower Na + content than YG. Conversely, the K + and Ca 2+ contents and the K + /Na + and Ca 2+ /Na + ratios decreased, but GG exhibited higher values than YG. GG reduced Na + by absorption by increasing tillers. Additionally, GG absorbed more K + and Ca 2+ ions, thereby maintaining higher K + /Na + and Ca 2+ /Na + ratios than YG under saline-alkaline stress. These adaptive strategies enable ecotype GG to grow and maintain normal physiological functions under high saline-alkaline stress. The findings of this study hold practical significance for enhancing the economic and ecological value of saline-alkaline grasslands.